Diferentes sons do trovão: uma perspectiva comparativa entre os deuses Thor, Ukko e Horagalles - Alves, Victor Hugo Sampaio (2019)
Thor, Ukko and Horagalles are, respectively, the Norse, Finnic and Saami thunder gods. The present study aims to investigate some of the main primary sources which mention those gods or that present any kind of mythological narrative concerning them, evidencing the most elementary traits and attributes given to them in such sources. In an attempt to capture the mythological, symbolical and cultural dimensions of these divinities, we are going to analyse their insertion in literary works belonging to their specific historical and cultural contexts, offering beforehand the necessary contextualization and critics of such materials. Secondly, we are going to present the convergences and divergences observed once these three gods, their descriptions and attributes are put in a comparative perspective. In order to do so, the comparative methodology as proposed by Schjødt will be adopted. More specifically, and according to the author, we are going to execute the so-called third level comparativism: when a comparison is done between the Norsemen and other polytheistic peoples with whom they have historically been connected. The notion of semanticcentres will also be used as a tool to help us identify the identification categories given to these gods within the respective mythical discourses they belong to.